Peran Customer Online Review dalam Memediasi Niat Beli Produk Skincare - Yandi Suprapto; Golan Hasan; Feby (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research examines the influence of digital marketing on purchase intention in the skincare industry, focusing on the role of social media marketing, e-WOM, brand image, and influencer endorsers mediated by customer online reviews. According to Statista (2020), the skincare industry experienced significant growth with a total value reaching USD 335.6 billion in 2020, increasing by 3.6% from the previous year and projected to reach USD 344.4 billion in 2021. This research aims to analyze the causal relationships between digital marketing variables (social media marketing, e-WOM, brand image, influencer endorsers) on purchase intention with customer online reviews as a mediating variable. The research method uses a quantitative approach with path analysis to test nine proposed hypotheses. The results show that SMM, e-WoM, and Brand Image have a significant influence on Customer Online Review, while Influencer Endorser shows no significant influence. This research extends previous studies by integrating the role of customer online reviews as a mediator in influencing consumer purchase intention